The Revalorization of Fishery By-Products: Types, Bioactive Compounds, and Food Applications - Diana Jimenez-Champi; Frank L. Romero-Orejon; Ana María Muñoz; Fernando Ramos-Escudero (International Journal of Food Science)
Recently, fish consumption has been increasing; subsequently, the number of by-products has also increased. However, generated residues are frequently discarded, and an appropriate management is necessary to properly use all fish by-products. Fishery by-products are well known for their content of bioactive compounds, such as unsaturated fatty acids, amino acids, minerals, peptides, enzymes, gelatin, collagen, and chitin. Several studies have reported that fishery by-products could provide significant properties, including antioxidant, antihypertensive, antimicrobial, anti-inflammatory, and antiobesity. Consequently, fish discards are of considerable interest to different industrial sectors, including food, nutraceuticals, medical, and pharmacology. In the food industry, the interest in using fishery by-products is focused on hydrolysates as food additives, collagen and gelatin as protein sources, chitin and chitosan to form edible films to protect food during storage, and oils as a source of Omega-3 and useful as antioxidants. Although different studies reported good results with the use of these by-products, identifying new applications in the food sector, as well as industrial applications, remains necessary.